Analisis Faktor Stres Kerja Terhadap Kinerja Karyawan (Studi pada (ABK) Kapal AKRA 90 PT. AKR Sea Transport) - Cici, Cici; Firayanti, Yuni; Mahardhika, Tubagus (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The aim of this research is to determine the factors of work stress in ship crew employees (ABK) and determine the effect of work stress on employee performance. The method used in this research is a qualitative research method with a phenomenological research model and the data obtained is based on the results of interviews and documentation. Data collection techniques use qualitative analysis techniques. The informants in this research were nine crew members (ABK) of the Akra 90 PT ship. AKR Sea Transport. In this research, the results obtained show that the work stress factors experienced (ABK) that can influence employee work stress are environmental factors with indicators of economic uncertainty, organizational factors with indicators of task demands, personal factors with indicators of family problems. Factors that influence employee work stress do not affect employee performance in a normal context and can still be overcome by employees.